1992
DOI: 10.1007/bf03009042
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine 0.1% does not improve postoperative epidural fentanyl analgesia after abdominal or thoracic surgery

Abstract: Epidural infusions of fentanyl, in a 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 26 publications
5
15
0
Order By: Relevance
“…This was in ac cor dan ce with a pre vi o us study in which it was de mons tra ted that the to tal do se of lo cal ana est he tic de ter mi ned the qu a lity of analge si a. 25 Pre o pe ra ti ve epi du ral anal ge sic tre at ment is mo re ef fec ti ve in ma na ging acu te pos to pe ra ti ve pa in, at te nu a ting pa in sco res, and dec re a sing the to tal supp le men tal anal ge sic con sump ti on. The refo re, our re sults sup port the conc lu si on that preemp ti ve epi du ral anal ge si a is ef fec ti ve and cli ni cally use ful in re du cing pos to pe ra ti ve pa in inten sity sco res.…”
Section: Discussionsupporting
confidence: 62%
“…This was in ac cor dan ce with a pre vi o us study in which it was de mons tra ted that the to tal do se of lo cal ana est he tic de ter mi ned the qu a lity of analge si a. 25 Pre o pe ra ti ve epi du ral anal ge sic tre at ment is mo re ef fec ti ve in ma na ging acu te pos to pe ra ti ve pa in, at te nu a ting pa in sco res, and dec re a sing the to tal supp le men tal anal ge sic con sump ti on. The refo re, our re sults sup port the conc lu si on that preemp ti ve epi du ral anal ge si a is ef fec ti ve and cli ni cally use ful in re du cing pos to pe ra ti ve pa in inten sity sco res.…”
Section: Discussionsupporting
confidence: 62%
“…Six patients ( ~W O ) were demonstrated to have a functioning epidural in the immediate postoperative period which subsequently failed. This is a disappointing failure rate compared with George and colleagues [4], though similar to Badner and Komar [19]. The level of anaesthetic intervention was quite high (required in 35% of patients) which illustrates the fact that whilst providing excellent pain relief, epidural infusions are labour intensive for anaesthetists.…”
Section: Discussionmentioning
confidence: 63%
“…In the similar study done by Behera et al 18 in 2008, comparison between IVPCA with morphine and PCEA with fentanyl and bupivacaine was done after thoracotomy procedures. They found that PCEA using fentanyl and bupivacaine provided better pain relief both at rest and during coughing and was associated with fewer side effects as compared to IV PCA using morphine.…”
Section: Discussionmentioning
confidence: 97%